Relationship Between Learning Style and Critical Thinking Skill Through Hybrid Learning on the Topic of Work and Energy - Mulhayatiah, Diah; Ayuningrat, Hilda Sulasi; Hidayatulloh, Rizki; Rochman, Chaerul (KnE Social Sciences, 2024)
Critical thinking skill is one of the abilities that must be possessed by students in the 21st century. Students are currently not trained to always think critically, which could be caused by the learning styles of the students themselves. The learning style here is a combination of a person’s state of being able to absorb, be able to organize, and be able to process information. This study aims to analyze the implementation and relationship of learning styles with critical thinking skills after the hybrid learning model is applied to the work and energy materials. The method used correlation analysis with product-moment correlation. The sample of this research was the students of class X MIPA, totaling 16 students who were selected by using the saturated sampling technique. The instruments used were a learning style questionnaire (an authentic assessment based on teaching and learning trajectory) with student activity sheet (AABTLT with SAS), and critical thinking skills test questions. The results showed that the average percentage of learning implementation using the hybrid learning model was 91% with a very effective category. The results of the hypothesis test using the product-moment correlation test, then count (0.110) < table (0.497) or count less than stable, so Ha is rejected and H0 is accepted. The results of this study can conclude that there is no significant relationship between learning styles and critical thinking skills of students of class X MIPA on the matter of work and energy. Keywords: learning style, critical thinking skill, hybrid learning